Hedging Effectiveness of Malaysian Crude Palm Oil Futures Contracts : The Extended Mean-Gini Framework - Tarn, Ju Yau (2013)
The stochastic dominance model has long been proven to exhibit greater theoretical advantage than the Minimum-Variance (MV) approach in futures hedging. This paper aims to demonstrate the superiority of Extended Mean-Gini (EMG) framework which is consistent with the secondorder of stochastic dominance theory. The merits of the EMG model are credited to its specifications where the distributional assumptions of normality are not required. The study provides a comprehensive analysis of investors’ distinct risk averse behaviour towards optimal futures hedging strategy. The empirical distribution function method and the more efficient kernel estimation method are employed in the estimation of EMG hedge ratios. Furthermore, in order to investigate the suitability of ‘buy and hold’ strategy in futures hedging, the moving data window procedure is used to examine the stability of the dynamic hedge ratios. The research is conducted on Malaysian Crude Palm Oil (CPO) and CPO Futures (FCPO) markets for the period of 16th March 1995 to 28th June 2011. The empirical results show that the EMG approach is apparently more appropriate than the MV approach where EMG framework incorporates the risk aversion factor. The study also shows the instability of dynamic hedge ratios across time horizons hence not favourable to investors who adopt the ‘buy and hold’ strategy.